Pengaruh Budaya Kerja, Komitmen Kerja, dan Kepuasan Kerja Terhadap Prestasi Kerja Pegawai Pada Dinas Kepemudaan Dan Olahraga Kota Batam - Hidayat, Topan; Riza, Amril Al; Hidayat, Samsul; Sabri, Sabri; Mulyadi, Mulyadi (eScience Humanity Journal, 2024)
This study aims to examine the impact of independent variables, namely self-efficacy (X1), job satisfaction (X2), and work engagement (X3), on the dependent variable, employee performance (Y), at the Youth and Sports Office of Batam City, both individually and collectively. The population of this study consists of all civil servant employees at the Youth and Sports Office of Batam City, totaling 60 people. No classification based on the type or status of the employees is made, as both categories receive the same treatment. The sample was selected using a census technique, meaning all members of the population were included in the sample. Therefore, the sample size is 60 people. The results of the study show a significant positive effect of self-efficacy (X1), job satisfaction (X2), and work engagement (X3) on employee performance (Y), with an F-value of 53.977. This value is much higher than the critical F-value of 2.88 at a significance level of 0.05. The relationship between the four variables is represented by the multiple regression equation: Y = 15.993 + 0.057X1 + 0.164X2 + 0.460X3. Based on validity and reliability tests, all instruments met the required standards. Among the variables, work engagement had the most significant impact, with a coefficient of determination of 70.6%, indicating it as the primary factor influencing employee performance.